2007
DOI: 10.1007/s11695-007-9282-0
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Pulmonary Risk Assessment and Perioperative Management in Bariatric Surgery Patients

Abstract: Bariatric surgery has serious associated medical comorbidity and procedure-related risks and is, thus, considered an intermediate-to-high-risk non-cardiac surgery. Altered respiratory mechanics, obstructive sleep apnea (OSA), and less often, pulmonary hypertension and postoperative pulmonary embolism are the major contributors to poor pulmonary outcomes in obese patients. Attention to posture and positioning is critical in patients with OSA. Suspected OSA patients requiring intravenous narcotics should be kept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 53 publications
0
13
0
6
Order By: Relevance
“…OSA is commonly encountered in morbidly obese patients undergoing bariatric surgery with a prevalence of 76% to 96%, but only 15% to 19% of these patients have an established diagnosis of OSA [1][2][3]. There is an increasing amount of evidence suggesting that sleep apnea has a significant negative impact on both the perioperative and postoperative complications in these patients [2,[4][5][6][7]. Sedatives, analgesics, and anesthetics alter upper airway tone, and airway obstruction and death have been reported in patients with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…OSA is commonly encountered in morbidly obese patients undergoing bariatric surgery with a prevalence of 76% to 96%, but only 15% to 19% of these patients have an established diagnosis of OSA [1][2][3]. There is an increasing amount of evidence suggesting that sleep apnea has a significant negative impact on both the perioperative and postoperative complications in these patients [2,[4][5][6][7]. Sedatives, analgesics, and anesthetics alter upper airway tone, and airway obstruction and death have been reported in patients with OSA.…”
Section: Introductionmentioning
confidence: 99%
“…Even though the respiratory pressures were normal, the values of respiratory muscle endurance were below the lower limit of normal, a situation that could slow or compromise the postoperative evolution of obese individuals, especially those submitted to bariatric surgery. Determination of these variables in the preoperative could guide preoperative monitoring and minimize the risk of postoperative respiratory complications, such as atelectasis and alterations in respiratory mechanics during pulmonary gas exchanges [2] and worsening of comorbidities during anesthetic narcosis [3]. These easy-touse measures enable assessment during the pre and postoperative period as well as an evaluation of respiratory muscle evolution after weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…During general anesthesia, pulmonary gas exchanges and respiratory mechanics are impaired [2]; moreover, during the anesthetic-narcosis period, comorbidities such as obstructive apnea, which accompanies obesity, may be exacerbated, especially if there are previous respiratory alterations [3]. Therefore, spirometry assessment before bariatric surgery is recommended, since alterations in pulmonary function and in respiratory muscles may influence postoperative complications [4].…”
Section: Introductionmentioning
confidence: 99%
“…Flum et al 24 reported that the 30-day mortality rate of morbidly obese patients undergoing a Roux-en-Y gastric bypass or laparoscopic adjustable gastric banding was significantly higher in patients with preexisting OSA. Kaw et al 25 documented that OSA is a major contributor to poor pulmonary outcomes in the obese patient and that elevated head position increases the stability of the upper airway, hence decreasing the incidence of postoperative complications. Ballantyne et al 26 studied hospital record of 311 patients who underwent Roux-en-Y gastric bypass.…”
Section: Osa Is a Perioperative Risk Factor For Morbidly Obese Patientsmentioning
confidence: 99%